The effect of menthol rinsing before intermittent exercise on physiological, physical, and thermo-behavioral responses of male football referees in hot and humid environment - Maria Roriz; João Brito; Filipe J. Teixeira; Filipe J. Teixeira; Konstantinos Spyrou; Konstantinos Spyrou; Vitor Hugo Teixeira; Vitor Hugo Teixeira; Vitor Hugo Teixeira (Frontiers in Sports and Active Living, 2024)
IntroductionIn the current experiment, we aimed to evaluate whether eliciting pre-exercise non-thermal cooling sensations would alter perceptual measures, and physical and physiological responses in football referees.MethodsNine highly trained male football referees undertook two 45-minute intermittent exercise protocols in hot and humid conditions (34.2 ± 0.6°C, 62.5 ± 1.0% relative humidity). In a randomized counterbalanced crossover design, 1 of 2 beverages were given before the warm-up: a 0.01% menthol solution or a placebo noncaloric solution. Physical performance was quantified as total distance covered in each of the three 15-minute exercise blocks. Core temperature, heart rate, thermal sensation and thermal comfort were measured at rest and after each exercise block.ResultsNo changes were observed between trials and over time for distance covered. No main effect of mouth rinse was observed for core temperature and heart rate, but both increased over time in all conditions (P < 0.001). Thermal sensation and thermal comfort were significantly improved with menthol after mouth-rinsing (P < 0.05), but with no differences at any other time-point.DiscussionThese results indicate that non-thermal cooling oral stimuli provide immediate behavioral changes but may not influence physiological or physical responses in football referees, during intermittent exercise in hot and humid environments. Clinical Trial Registrationwww.clinicaltrials.gov, identifier NCT05632692.